(untitled) (Clinics, 2017)
OBJECTIVE: To evaluate the costs and patient safety of a pilot implementation of an automated dispensing cabinet in a critical care unit of a private tertiary hospital in São Paulo/Brazil. METHODS: This study considered pre- (January-August 2013) and post- (October 2013-October 2014) intervention periods. We considered the time and cost of personnel, number of adverse events, audit adjustments to patient bills, and urgent requests and returns of medications to the central pharmacy. Costs were evaluated based on a 5-year analytical horizon and are reported in Brazilian Reals (R) and US dollars (USD). RESULTS: The observed decrease in the mean number of events reported with regard to the automated drug-dispensing system between pre- and post-implementation periods was not significant. Importantly, the numbers are small, which limits the power of the mean comparative analysis between the two periods. A reduction in work time was observed among the nurses and administrative assistants, whereas pharmacist assistants showed an increased work load that resulted in an overall 6.5 hours of work saved/day and a reduction of R 33,598 (USD 14,444) during the first year. The initial investment (R 206,065; USD 88,592) would have been paid off in 5 years considering only personnel savings. Other findings included significant reductions of audit adjustments to patient hospital bills and urgent requests and returns of medications to the central pharmacy. CONCLUSIONS: Evidence of the positive impact of this technology on personnel time and costs and on other outcomes of interest is important for decision making by health managers.